INCREASING TEACHERS' COMPETENCE THROUGH WEB-BASED INTERACTIVE MEDIA TRAINING IN MATHEMATICS LEARNING - Teti Trisnawati; Sastra Wijaya (LPM Universitas Pasundan, 2021)
Community Service Program (PKM) Improving Teacher Competence Through WEB-Based Interactive Media Training in Mathematics Learning aims to overcome the problems faced by SMAN 1 Bayah. The limited basic knowledge of teachers regarding interactive media that can be used to support the passage of an effective teaching and learning process, especially WEB-based. The solution offered is to provide mentoring and training to teachers directly regarding WEB-based interactive media. The training aims to improve teacher competence through WEB-based interactive media training in mathematics learning. The training activities are carried out for 5 (five) days by reviewing the plan of learning and training programs as well as guidance in creating and running the WEB in its role to support the learning process. The results of this PKM showed an increase in scientific capacity and competence by 19.8% for WEB-based interactive media training in Mathematics learning at SMAN 1 Bayah.